Asian food processing industries (Tokyo, 1978)
This book introdce reports on APO regional survey, other symposium papers. Country reports on the status of the food processing industry in Asia.
Keywords: Công nghiệp thực phẩm và thương mại,Food industry and trade; Châu Á,Asia